Emerging Role of Circular RNAs in Cancer - Liu, Jing; Zhang, Xin; Yan, Meinan; Li, Hui (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs), which are mainly generated from precursor mRNAs (pre-mRNAs) back-splicing of exons, are a novel class of endogenous covalently closed RNA molecules. It is beginning to appreciate that they function as microRNA sponges, protein scaffolds, modulators of transcription and splicing, as well as templates to produce polypeptides occasionally, though the area of circRNAs investigation is in its infancy. CircRNAs play critical roles in diverse cellular processes. The aberrant expressions of circRNAs in malignancies sustain cellular growth and proliferation, promote invasiveness, as well as circumvent cellular senescence and death, suggesting that they will probably be developed as clinical biomarkers and therapeutic targets. In this review, we would highlight the recent progress in the field of circRNAs and cancer, emphasizing the molecular mechanisms of circRNAs and their potential values in clinical practice. Additionally, we would discuss the technologies in investigating circRNAs in cancer biology, hoping to inspire future research.